A test of improved force field parameters for urea: molecular-dynamics simulations of urea crystals - Ozpinar, Gul Altinbas; Beierlein, Frank; Peukert, Wolfgang; Zahn, Dirk; Clark, Timothy (Journal of Molecular Modeling, 2012)
Molecular-dynamics (MD) simulations of urea crystals of different shapes (cubic, rectangular prismatic, and sheet) have been performed using our previously published force field for urea. This force field has been validated by calculating values for the cohesive energy, sublimation temperature, and melting point from the MD data. The cohesive energies computed from simulations of cubic and rectangular prismatic urea crystals in vacuo at 300 K agreed very well with the experimental sublimation enthalpies reported at 298 K. We also found very good agreement between the melting points as observed experimentally and from simulations. Annealing the crystals just below the melting point leads to reconstruction to form crystal faces that are consistent with experimental observations. The simulations reveal a melting mechanism that involves surface (corner/edge) melting well below the melting point, and rotational disordering of the urea molecules in the corner/edge regions of the crystal, which then facilitates the translational motion of these molecules.